Transformasi Sistem Irigasi Subak yang Berlandaskan Konsep Tri Hita Karana - Wayan Windia; Suprodjo Pusposutardjo; Nyoman Sutawan; Putu Sudira; Sigit Supadmo Arief (agriTECH, 2003)
Subak irrigation system beside as an appropriate technological system, but as a cultural system as well. This fenomenon indicate that basically subak irrigation system is a technological system that has been developed as a part of cultural society. Because of subak system is viewed as a technological system, so this system has an ability to be transformed. Meanwhile, limitation of the ability of subak irrigation system to overcome the ezireem conditions, so its conditions basically to be solved through the harmony and togetherness, due to the Tri Hita Karana (THK) principles as a basic of subak system. Futhermore, through inverse technique, can be seen how far the ability of subak system can be transformed. And then, through Fuzzy Set Theory can be seen the dominance or ranks of the all elements of subak system, which is also as a consideration on the transformation process. (THK) principles as a basic of subak system. Futhermore, through inverse technique, can be seen how far the ability of subak system can be transformed. And then, through Fuzzy Set Theory can be seen the dominance or ranks of the all elements of subak system, which is also as a consideration on the transformation process.